Vivendo o bem estar no desconhecido: experiência da mulher com a presença do acompanhante no processo de parto - Costa, Maria Cláudia Medeiros Dantas de Rubim (2007)
The humanization of the birth process is a current health policy priority. Within that perspective, the presence of a partner during the birth is a benefit guaranteed by the Law 111008/05. The purpose of this study is to comprehend the woman s experience with the presence of a birth partner as a legal right. It is a qualitative descriptive study based on Symbolic Interactionism and conducted using the grounded theory methodology. Data were collected by semi-structured interviews conducted during August to December 2006, with women that had the presence of a partner during their birth experience and that were in the first 24 hours of puerperium. Data analysis resulted in the identification of the phenomena: FEELING GOOD, RECOGNIZING THE BOND WITH THE PARTNER, RECOGNIZING THE IMPORTANCE OF THE EXPERIENCE and NOT KNOWING THE RIGHT. These enabled the identification of the central phenomenon LIVING THE WELL-BEING IN THE UNKNOWN. The study demonstrated that the birth experience with the presence of partner is a positive one, resulting in benefits such as tranquility, support, and assurance, which, in that context, signify well-being. However, the women do not visualize the experience as a right, therefore remaining alienated from their civic practice. The understanding of the experience was enabled by the conceptual construction obtained from the categories of the interactions between the women and their birth partners during the event. The explanation of the phenomenon LIVING THE WELL-BEING IN THE UNKNOWN reflects the theoretical structure obtained from the integration of the identified concepts. The study points out the need for health professionals to improve the information given to women during the birth process and to work the civic duties of the women in reproductive health